DA'WA ACTIVITIES OF VEILED WOMEN (NIQAB) ON INSTAGRAM - Ira Wahyudi (al-Balagh : Jurnal Dakwah dan Komunikasi, 2021)
Veiled women in Indonesia invite various perspectives in society. This is more or less influenced by the differences of opinion regarding the understanding of the veil (niqab). However, veiled (niqab) women certainly have the same rights as other people who do not wear the veil (niqab). They also have the right to be active and keep up with the times and technology that is increasingly sophisticated and make it possible to introduce themselves through the development of such technologies as Instagram. Besides, veiled (niqab) women can obtain the benefit of Instagram as a medium of da'wa as one of their wasilah and hope to be accepted by the public. This study conducted a qualitative descriptive approach that aimed to obtain the actual information in detail that described the existing symptoms. The results of this study described the activities of veiled (niqab) women in uploading Islamic content in the majority of 1-2 times a day. The topics raised included aqidah, morality, and daily life. The expectations of women participants who actively in da'wa through Instagram can be slowly accepted by the wider community and are no longer viewed with a negative stigma.